2020
DOI: 10.3390/ani10101752
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthesia in Piglets Undergoing Castration—A Comparative Study to Investigate the Analgesic Effects of Four Local Anesthetics Based on Defensive Behavior and Side Effects

Abstract: The aim of the present study was to investigate the effect of four local anesthetics on pain relief during surgical castration under standardized conditions in conscious piglets. Therefore, 71 male piglets (three to seven days) were distributed into control groups (handling, castration without anesthesia or analgesia) and local anesthetic trial groups (procaine, lidocaine, bupivacaine, mepivacaine). Then, 20 min prior to castration, animals of the treatment groups, except piglets in the handling group, receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…Similar observations have been made after performing several procedures consecutively in piglets [23,25]. Our results confirm previous studies [10,11], indicating that particularly the kind of body movement can be considered a reliable indicator for the assessment of pain and distress during the castration of piglets, as it is able to determine differences between different castration techniques and pain treatments.…”
Section: Effects Of Castration Technique and Event On Vocalizations Asupporting
confidence: 90%
See 3 more Smart Citations
“…Similar observations have been made after performing several procedures consecutively in piglets [23,25]. Our results confirm previous studies [10,11], indicating that particularly the kind of body movement can be considered a reliable indicator for the assessment of pain and distress during the castration of piglets, as it is able to determine differences between different castration techniques and pain treatments.…”
Section: Effects Of Castration Technique and Event On Vocalizations Asupporting
confidence: 90%
“…Therefore, it was not possible to numerically determine sound parameters such as entropy, energy or frequency and the generated data is not fully comparable to other study results. Similarly, Abendschön et al [11] applied a more practical approach by determining an acute onset of vocalization by human hearing. They, however, did not further categorize the perceived sounds.…”
Section: Effects Of Castration Technique and Event On Vocalizations Amentioning
confidence: 99%
See 2 more Smart Citations
“…Animals treated with COP-THB/LDC showed rapid onset of local anesthesia. After we confirmed that COP-THB/LDC has a longer retention time than COP-THB solution, we investigated the local anesthetic effect of COP-THB/LDC in vivo (Abendsch€ on et al, 2020). We used carrageenan (CGN)-induced inflammation on the RHP.…”
Section: Anesthetic Effect Of Cop-thb/ldcmentioning
confidence: 99%